Molecular environs and triggered star formation around the large Galactic infrared bubble N 24. Issue 2 (4th June 2019) - Li, Xu; Esimbek, Jarken; Zhou, Jianjun; Baan, W A; Ji, Weiguang; Tang, Xindi; Wu, Gang; Tang, Xiaoke; Li, Qiang; Ma, Yingxiu; Sailanbek, Serikbek; Li, Dalei; et al.
Abstract: A multi-wavelength analysis of the large Galactic infrared bubble N 24 is presented in this paper in order to investigate the molecular and star-formation environment around expanding H ii regions. Using archival data from Herschel and ATLASGAL, the distribution and physical properties of the dust over the entire bubble are studied. Using the Clumpfind2d algorithm, 23 dense clumps are identified, with sizes and masses in the range 0.65–1.73 pc and 600–16 300 M⊙, respectively. To analyse the molecular environment in N 24, observations of NH3 (1, 1) and (2, 2) were carried out using the Nanshan 26-m radio telescope. Analysis of the kinetic temperature and gravitational stability of these clumps suggests gravitational collapse in several of them. The mass–size distributions of the clumps and the presence of massive young protostars indicate that the shell of N 24 is a region of ongoing massive-star formation. The compatibility of the dynamical and fragmentation timescales and the overabundance of young stellar objects and clumps on the rim suggest that the 'collect-and-collapse' mechanism is in play at the boundary of the bubble, but the existence of the infrared dark cloud at the edge of bubble indicates that a 'radiation-driven implosion' mechanism may also have played a role there.